Characterization of superparamagnetic iron oxide nanoparticles and their effect on viability in cancer and non-cancerous cell-lines - Viviana Sandoval-Flores; J Angelica Ortega-Cardenas; Eva Ramon-Gallegos; Gustavo F Gutiérrez-López; David Ravelo-Acuña; Hernani Yee-Madeira; Rosalva Mora-Escobedo (Materials Research Express)
Superparamagnetic iron oxide nanoparticles (SPION) have demonstrated potential biomedical application, mainly for cancer treatment. In this work, SPION were successfully synthesized by the coprecipitation method, followed by coating and functionalization with 3-aminopropyl- triethoxysilane (APTES). The synthesized samples (SPION and SPION@APTES) were characterized by their microscopic morphology, electrical charge, composition, and their superparamagnetic behavior was confirmed by SQUID analysis. The aqueous stability of SPION and SPION@APTES was significantly improved upon APTES coating, enhancing their potential as therapeutic molecules. Evaluation of cell viability upon exposure to SPION was assessed through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in three cell- lines (non-tumoral HaCaT, tumoral cervical HeLa, and MDA-MB-231 breast cancer). HeLa cells showed greater tolerance to both samples of SPION than the other cell lines. Conversely, MDA- MB-231 and HaCaT cells showed significant differences between SPION and SPION@APTES. A dose-dependent decrease in cell viability was observed in the three cell-lines at concentrations >200 μg ml ^−1 for both samples SPION and SPION@APTES. It was demonstrated that dosage, exposure time, and the use of specific cell-lines must be considered when assessing SPION toxicity and its therapeutic potential.